Touching at a Distance: Resistance, Tactility, Proxemics and the Development of a Hybrid Virtual/Physical Performance System. - Waters, Simon (Contemporary Music Review, 2013)
This is a paper about resistance and affordance as they relate to music-making in the most extended sense, and perhaps about empathy if this is understood as a capacity to ‘read’ the resistances and affordances of objects, bodies, people, and environments. It proceeds from a set of broad working assumptions which inform one individual's musical practice, via description of a musical-instrument-making project which is a hybrid of physical and virtual elements and is designed to test those assumptions, to a speculative finale in which it is suggested that musicking might, in some circumstances, be regarded in itself as a form of resistance. It moves from the intimate and personal, through what might be regarded as local concerns to more global observation, prefiguring the structure of the performance system it describes: the Virtual-Physical Feedback flute.